Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I want to show that $$ \sum_{i=0}^n {n\choose i} \left(x^{i+1}y^{n-i} + x^i y^{n-i+1}\right) = \sum_{i=0}^{n+1}{n+1 \choose i}x^i y^{n+1-i}. $$ I was thinking to split the sum on the LHR into 2 sums and then perform an index transformation on the first sum, so I would be able to use Pascal's rule. Unfortunately I wasn't able to find the right transformation so far, as I always end up with something like $\sum_{i=0}^{n+1}{n\choose i-1}$ for the first sum, which doesn't make sense for the binomial coefficient (because $i-1=-1$).

Any hints?

share|cite|improve this question
up vote 1 down vote accepted

If you apply the recurrence on binomial coefficients, you have two choices:

You think of $\dbinom n {-1}$ as undefined and you have to take great care not to apply the recurrence to $\dbinom n 0$ (which you tried to do), or you just define $\dbinom n {-1} = 0$ and then you are allowed to always apply the recurrence (which is much better for calculation).

(Note that it isn't necessary to apply the recurrence for this particular exercice, but it is absolutely allowed.)

share|cite|improve this answer

$$ \sum_{i=0}^n {n\choose i} \left(x^{i+1}y^{n-i} + x^i y^{n-i+1}\right) $$

$$= x\sum_{i=0}^n {n\choose i} \left(x^{i}y^{n-i}\right)+y\sum_{i=0}^n {n\choose i} \left(x^{i}y^{n-i}\right)$$


$$ =\sum_{i=0}^{n+1}{n+1 \choose i}x^i y^{n+1-i}. $$

share|cite|improve this answer

May be you can calculate as following:

$$\begin{align*} \sum_{i=0}^{n}{n\choose i}\left(x^{i+1}y^{n-i}+x^i y^{n-i+1}\right) &=\sum_{i=0}^{n}{n\choose i}x^{i+1}y^{n-i}+\sum_{i=0}^{n}{n\choose i}x^i y^{n-i+1}\\ &=\sum_{i=1}^{n+1}{n\choose i-1}x^{i}y^{n-i+1}+\sum_{i=0}^{n}{n\choose i}x^i y^{n-i+1}\\ &=\sum_{i=0}^{n+1}{n\choose i-1}x^{i}y^{n-i+1}+\sum_{i=0}^{n+1}{n\choose i}x^i y^{n-i+1}\\ &=\sum_{i=0}^{n+1}\left[{n\choose i-1}+{n\choose i}\right]x^{i}y^{n-i+1}\\ &=\sum_{i=0}^{n+1}{n+1\choose i}x^i y^{n+1-i} \end{align*}$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.